Diagnosis and management of green algae in low land paddy fields of Cauvery delta zone, Tamil Nadu - Jeya Bharathi, M; Raju, M; Elamathi, S (ORYZA-An International Journal of Rice, 2021)
Rice is a prime food crop for Asian countries. Wet land rice cultivation contributes maximum grain yield than dry land rice. Cauvery delta is a predominant area for rice cultivation in Tamil Nadu. Green algae growthduring Kuruvai (June -August) season is a serious problem in wet land rice. These algae growth create anaerobic condition and prevent rice root respiration. The entire rice root was uprooted and floated on the stagnated water during initial stage. There is no preliminary study for green algae control in rice field. Soil and water samples were collected and analyzed for the nature of occurrence. Laboratory and field experiments were conducted to find out the remedial measures. The results of soil and water sample analysis showed that use of bore well water and dumping of phosphatic fertilizers leads to salt accumulation which favours the green algal growth. The results of the laboratory experiment revealed that the CuSO4 londox power, propiconazole andhexaconazole showed moderate inhibition on 5th day after treatment. The findings from field experiment indicated that use of conoweeder, alternate wetting and drying and CuSo4 drenching @ of 2.5 kg/ha when green algaeappearance has just noticed or 5.0 kg/ha when severe growth occurred was effective in managing the green algae. Among all measures, alternate wetting and drying is the best management practices. CuSO4 drenching reduces around 70% of the growth. Even though CuSO4 react negatively with algae growth, soil pH changes and salt concentration play a major role on the CuSO4 action towards green algae. In order to maintain soil health condition, biofertilizer application, crop rotation, green manure trampling to be practised to recover the soil from alkaline pH, removal of accumulated salt and to control the algae growth using CuSO4.